2022
DOI: 10.1093/gerona/glac091
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Human Lung Mucosa: A Proteomics Study

Abstract: The older adult population, estimated to double by 2050, is at increased risk of respiratory infections and other pulmonary diseases. Biochemical changes in the lung alveolar lining fluid (ALF) and in alveolar compartment cells can alter local immune responses as we age, generating opportunities for invading pathogens to establish successful infections. Indeed, the lung alveolar space of older adults is a pro-inflammatory, pro-oxidative, dysregulated environment that remains understudied. We performed an explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…First, we normalized the ALF samples based on their physiological phospholipid content within the lung as we described previously (21, 2629, 3133, 42, 43). To analyze the effects of oxidative stress in the lung environment of PLWH, we measured carbonyl and 3-nitrotyrosine protein modification in control- and HIV-ALFs, indicators of irreversible protein oxidation by ROS and RNS, respectively ( Fig 1A, B ) (21, 32, 33, 44).…”
Section: Resultsmentioning
confidence: 99%
“…First, we normalized the ALF samples based on their physiological phospholipid content within the lung as we described previously (21, 2629, 3133, 42, 43). To analyze the effects of oxidative stress in the lung environment of PLWH, we measured carbonyl and 3-nitrotyrosine protein modification in control- and HIV-ALFs, indicators of irreversible protein oxidation by ROS and RNS, respectively ( Fig 1A, B ) (21, 32, 33, 44).…”
Section: Resultsmentioning
confidence: 99%
“…The elderly population is considered a large reservoir for M.tb infection due to their increased vulnerability to active TB disease or reactivation of latent TB (7, 8). We have published that the lung mucosa or ALF from elderly individuals (65+ years old) is highly oxidized and constitutes a pro-inflammatory environment with dysfunctional innate proteins (1214), and that M.tb replicates faster upon contacting the elderly lung mucosa (E-ALF) in human macrophages and can replicate to a higher bacterial load in mice, leading to more extensive lung tissue damage (13). More recently, we reported that M.tb exposure to E-ALF enhances intracellular growth in ATs and alters endosomal trafficking with increased bacterial translocation into the cytosol (15).…”
Section: Discussionmentioning
confidence: 99%
“…The increased susceptibility of the elderly to TB may be attributed to age-related alterations in the lung environment, including innate soluble components of the ALF. Our research has shown that aging impacts the pulmonary environment by causing a shift towards a pro-inflammatory and pro-oxidative state, thus reducing the functionality of soluble innate immune proteins such as SP-A and –D (1214). Age-associated alterations in ALF components and their functional status are linked to decreased ability of phagocytes to control M.tb infection in vitro and in vivo (13, 15).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammaging was originally characterized as a persistent low-grade pro-inflammatory state in the circulation that progressively increases with age [ 31 ], interfering with regulation of anti-inflammatory responses, driving immuno-senescence, and increasing the risk of chronic diseases as an individual ages [ 30 , 32 ]. The molecular composition of the alveolar lining fluid (ALF) components (e.g., innate soluble protein/cytokines and lipids) in the lung are also significantly altered in aged mice and elderly humans, resulting in a relatively oxidized environment [ 27 , 33 , 34 ]. Such studies confirmed that inflammation is not limited to the periphery, but can also be found within the lung and, likely, within other tissues too.…”
Section: Inflammaging And/or Immuno-senescence?mentioning
confidence: 99%